Feasibility of Motivational Interviewing and Physical Activity Counseling Sessions for Improving Physical Activity Self-Management for Latina Women Either at Risk for or Diagnosed With Type 2 Diabetes Mellitus. (September 2019) - Soderlund, Patricia D.; Stuart, Gail W.; Mueller, Martina; York, Janet; Lopez, Cristina M.
Introduction: Latinas have a greater chance of dying from diabetes than non-Latina Whites. As a population group, the literature has shown that Latinas do not meet physical activity (PA) guidelines. Motivational interviewing (MI) is a patient-centered counseling method that promotes self-efficacy for behavior change. The purpose of the study was to examine the feasibility of using MI/PA counseling for self-management of type 2 diabetes mellitus with Latinas.Methods: Latinas ( n = 12) were recruited from an occupational program in Southern California. Two MI and PA sessions were conducted over 2 months. Feasibility measures included recruitment, retention, protocol adherence, and attrition. Impact outcomes included PA, PA stage of change, and waist circumference.Results: Participants attended all sessions and completed all questionnaires. Half progressed into a later stage of change for PA.Discussion: Results suggest MI and PA counseling is feasible for improving PA with Latinas at risk/diagnosed with type 2 diabetes mellitus.